Magnetic resonance imaging characteristics in patients with psoriatic arthritis and axial manifestations from the MAXIMISE cohort - Baraliakos, X; Pournara, E; Coates, LC; Navarro-Compán, V; Blanco, R; O’Brien, E; Schulz, B; Landewe, R (Oxford University Press, 2023)
Objective: The current analysis of the MAXIMISE trial was conducted to investigate the presence of post-inflammatory and degenerative spinal changes and inflammatory changes in spinal processes identified in baseline MRIs and their potential for predicting differential treatment effects in a cohort of PsA patients with axial manifestations. Methods: Baseline spinal MRIs from the MAXIMISE trial were re-read to identify additional inflammatory (spinal process), post-inflammatory, and degenerative changes, and investigate the differential treatment effect of these imaging features using logistic regression modelling. Results: In addition to bone marrow oedema assessed at primary analysis, spinal process inflammation and post-inflammatory changes evaluated by FAt Spondyloarthritis Spine Score were documented in 11.1% and 20.2% patients, respectively. At least one type of degenerative change was noted in 64% patients, with Pfirrmann grade ≥3 (51.1%) being the most common. Combining primary and re-read MRI findings, 67.1% of patients presented with inflammatory or post-inflammatory changes while 21.2% had degenerative changes alone. Although not statistically significant, post-inflammatory changes were associated with a trend for better efficacy outcomes in terms of ASAS20, ASAS40 and BASDAI50 responses; a trend for worse outcomes was observed in the presence of degenerative changes. Conclusion: The current analysis revealed the occurrence of additional inflammatory and post-inflammatory changes suggestive of axial PsA (axPsA) and a trend for better clinical outcomes for patients treated with secukinumab. These results elucidate the imaging characteristics and improve our current understanding of axPsA thereby supporting the interpretation of future trials. Trial registration: ClinicalTrials.gov, NCT02721966.